Did the relative age effect change over a decade in elite youth ski racing? - Steidl-Müller, L.; Müller, E.; Hildebrandt, C.; Raschner, C. (Frontiers in Sports and Active Living, 2019)
The relative age effect (RAE) represents an asymmetry in birth quarter distribution, favoring athletes born early in the selection year and discriminating against late born athletes. The RAE was proven to be present in all age categories of national and international levels of alpine ski racing. Due to the existence of the RAE in all categories, it can be assumed that a selection error takes place favoring early born and early maturing youth ski racers. However, whether selection strategies have changed during the last years due to the high amount of research done in this field, has not been investigated so far in this sport. Therefore, the aim of the present study was to assess whether the magnitude of the RAE in youth ski racers aged 10-14 years has changed during the last decade by comparing the periods 2005-2009 ("former" athletes) and 2015-2019 ("current" athletes). Pupils of a well-known skiing-specific secondary modern school as well as members of the provincial ski team, who all competed at national levels, were included in the study. Next to the birth months, anthropometric characteristics (body height, weight, body mass index) were assessed. Chi-square tests were used to compare differences between the observed and expected relative age quarter distributions across five age categories (U11-U15). Additionally, Kruskal-Wallis-H-Tests were performed to assess differences in anthropometric characteristics between athletes of the four relative age quarters. Mann-Whitney U-Tests were performed to assess possible differences in anthropometric characteristics between former and current ski racers. A highly significant RAE was present in both former [Chi2(3, 764) = 60.36; p < 0.001; Omega = 0.31] and current youth ski racers [Chi2(3, 702) = 43.13; p < 0.001; Omega = 0.29] with an over-representation of athletes of Q1 (30.3-34.2%) and a clear under-representation of athletes of Q4 (14.8-15.0%). Generally, results indicated no change in the magnitude of the RAE in youth alpine ski racing over the past 10-15 years, emphasizing the robust nature of this phenomenon. No significant differences were found in any of the anthropometric characteristics between athletes of the four relative age quarters in both former and current athletes, indicating that relatively younger athletes of the last relative age quarter seem to have to have advanced anthropometric characteristics for being selected. Changes in the talent selection process should be performed to reduce the impact of the RAE.